Flame‐retardant compounds for polymeric materials from an abundantly available, renewable biosource, castor oil. (26th December 2019) - Howell, Bob A.; Ostrander, Eric A.
Summary: Castor oil is a triglyceride extracted from the seed (castor bean) of the castor plant. This plant will thrive on relatively poor soil and in an arid climate. The oil is nonedible but is produced annually in large volume to be converted to biodiesel (largely for the European market). The oil contains both unsaturation and hydroxyl functionality that may be utilized for conversion to flame retarding materials. A series of phosphorus esters has been generated from castor oil. All display good flame retardancy in the diglycidyl ether of bisphenol A (DGEBA) epoxy resin. Introduction of bromine at the double bond generally enhances the flame retardancy of these esters.